Mechanisms of hepatic ischemia-reperfusion injury and protective effects of nitric oxide - Guan, Lian-Yue (World journal of gastrointestinal surgery, 2014)
Hepatic ischemia-reperfusion injury(IRI) is a patho-physiological event post liver surgery or transplantation and significantly influences the prognosis of liver func-tion. The mechanisms of IRI remain unclear, and effec-tive methods are lacking for the prevention and therapy of IRI. Several factors/pathways have been implicated in the hepatic IRI process, including anaerobic metabo-lism, mitochondria, oxidative stress, intracellular cal-cium overload, liver Kupffer cells and neutrophils, and cytokines and chemokines. The role of nitric oxide(NO)in protecting against liver IRI has recently been report-ed. NO has been found to attenuate liver IRI through various mechanisms including reducing hepatocellular apoptosis, decreasing oxidative stress and leukocyte adhesion, increasing microcirculatory flow, and enhanc-ing mitochondrial function. The purpose of this review is to provide insights into the mechanisms of liver IRI, indicating the potential protective factors/pathways that may help to improve therapeutic regimens for control-ling hepatic IRI during liver surgery, and the potential therapeutic role of NO in liver IRI.